The Adolescent Ruminative Response Scale (Thai version): Psychometric Properties - Thanoi, Wareerat; Panitrat, Rungnapa; Phancharoenworakul, Kobkul; Thompson, Elaine A; Nityasuddhi, Dachavudh (Nursing Science Journal of Thailand, 2011)
Purpose: This study aimed to evaluate the psychometricproperties of the Rumination Response Scale (RRS) in the Thaiyouths. Design: A methodological research. Methods: Following translation and cross-cultural adaptation, theRRS was tested on 1,417 adolescents aged ranging from 14 to 19years and attending the schools of Bangkok, Thailand. Data werecollected using a battery set of self-report questionnairesincluding the Thoughts, Feelings and Experiences Questionnaireand the Rumination Response Scale. The relationship ofrumination to emotional distress and suicide risk behaviors fortesting the construct validity was investigated. Confirmatoryfactor analysis and content validity index were performed tovalidate the factor structure and the content of the RRS. Inaddition, Cronbach’s alpha coefficient was calculated forreliability. Main findings: The results revealed that the 3-factor structure ofthe RRS-Thai version fitted with the data well (χ2 = 0.094,df = 1, p = .759, GFI = 1.000, AGFI = 1.000, RMSEA = 0.000).The RRS-Thai version showed good content validity (CVI = .95)and internal consistency (α = .90). In addition, the ruminationwas also positively correlated with emotional distress (r = .736, p< .01) and suicide risk behaviors (r = .46, p < .01). Conclusion and recommendations: The Rumination ResponseScale-Thai version showed satisfactory psychometric propertiesas to those of the original version and can be used for assessingThai adolescents at risk of suicide.